Bisnis Digital: Studi Kasus Penggunaan VTube, Jempol Preneur, dan Goins di Masa Pandemi Covid-19 - Rifqiani Nur Fadhillah (Universitas Muslim Maros, 2021)
The Covid-19 pandemic has not only created social fear, but has also affected various aspects of human life, including in the field of economy. To reduce the spread of Covid-19, the government issued a work from home (WFH) policy and study from home. This not only limits the interaction between people, but this condition also causes people to be creative and look for alternatives to earn income. One that has the potential to be done is a digital business, which is not only easy and simple (using gadgets and internet networks), but can also be done anywhere, especially at home because of the